Effects of arachidonic acid supplementation in maternal diet on low-salinity tolerance of newly hatched larvae of giant freshwater prawn (Macrobrachium rosenbergii De Man) - Kangpanich, C.; Pratoomyot, J.; Siranonthana, N.; Senanan, W. (International Journal of Agricultural Technology, 2017)
Arachidonic acid (20:4n-6, ARA) is an important fatty acid in giant river prawn reproduction. Improving larval quality may be possible through improved nutrition of maternal diets. The present study evaluated the effects of ARA supplementation in maternal diets on survival rates of newly hatched larvae exposed to six salinity levels (0, 2, 4, 6, 8, and 14 ppt) for 24 hours. Six experimental diet consisted of two base diets differing in fish oil (FO)/soy oil (SO) blends (A and B) and three ARA supplementation levels 0, 0.4 and 0.8%. The two diets diffred in the proportional contents of linoleic acid (18:2n-6, LOA, B>A) and docosahexaenoic acid (22:6n-3, DHA, A>B). At 2, 4 and 6 ppt, the survival rates at 24 hours of newly hatched larvae from females fed the diet with 0.8% ARA supplementation and higher LOA contents from SO (diet B2) were highest followed by those fed the B1 diet (0.4% supplemented ARA) (p<0.05) (B2=87.04, 93.32 and 98.88%; B1=79.23, 91.84 and 97.03 % for 2, 4 and 6 ppt respectively). Similarly, 24-hour LD50 values were lowest for the B2 treatment (0.80±0.02), suggesting their high tolerance to extremely low salinity levels. Our results have a great implication for an inland hatchery operation where seawater is a scarce resource.